Correlation Between Body Mass Index, Gender, and Age With Cholelithiasis : Correlation Between Body Mass Index, Gender, and Age With Cholelithiasis - Al Atsariyah, Fatimah; Parish Budiono, Bernardus; Mahati, Endang; Lestari Partiningrum, Dwi (RSUP Dr. Kariadi, 2022)
BACKGROUND : Gallstones are formed due to deposit or hypersaturation of one or more of the bile components, namely cholesterol, bilirubin, bile salts, calcium, protein, fatty acids, and phospholipids. BMI, gender, and age are the factors that can trigger the formation of gallstones. In Indonesia, cholelithiasis cases have received less attention because they are often asymptomatic, making it difficult to detect and often misdiagnosed, resulting in a lack of official publication about the incidence of gallstones in Indonesia. AIM : To determine the correlation between BMI, Gender, and Age with cholelitiasis in Dr. Kariadi Hospital. METHOD : This was an observational study using cross-sectional design. Data were taken from medical records of patients in Digestive Surgery Department Dr. Kariadi Hospital from January 2018 until March 2020. A total of 100 patients were selected as subjects (50 patients with cholethiasis and 50 patienst without cholelithiasis). Pearson Chi-Square correlation was used for statistical analysis. RESULTS : Pearson Chi-Square test of BMI (p = 0.001) and Age (p = 0.041) was statistically significant for cholelithiasis risk (p < 0.05). While Gender (p = 0.224) was not statistically significant for cholelithiasis risk. CONCLUSION : There wa a significant correlation between BMI and Age with Cholelithiasis and there was no significant correlation between Gender with Cholelithiasis. KEYWORDS : Body Mass Index (BMI), Gender, Age, Cholelithiasis.